Chitosan and its derivatives as promising plant protection tools - A. B. Shcherban (Вавиловский журнал генетики и селекции)
In modern conditions, the increase in the yield of agricultural crops is provided not by expanding the areas of their cultivation, but mainly by introducing advanced technologies. The most effective strategy for this purpose is the development of genetically resistant and productive cultivars in combination with the use of a variety of plant protection products (PPPs). However, traditional, chemical PPPs, despite their effectiveness, have significant drawbacks, namely, pollution of environment, ecological damage, toxicity to humans. Recently, biological PPPs based on natural compounds have attracted more attention, since they do not have these disadvantages, but at the same time they can be no less effective. One of such agents is chitosan, a deacetylation product of chitin, one of the most common polysaccharides in nature. The high biological activity, biocompatibility, and safety of chitosan determine the breadth and effectiveness of its use in medicine, industry, and agrobiology. The review considers various mechanisms of action of chitosan as a biopesticide, including both a direct inhibitory effect on pathogens and the induction of plant internal defense systems as a result of chitosan binding to cell surface receptors. The effect of chitosan on the formation of resistance to the main classes of pathogens: fungi, bacteria, and viruses has been shown on a variety of plant objects. The review also discusses various ways of using chitosan: for the treatment of seeds, leaves, fruits, soil, as well as its specific biological effects corresponding to these ways. A separate chapter is devoted to protection products based on chitosan, obtained by its chemical modifications, or by means of combining of a certain molecular forms of chitosan with various substances that enhance its antipathogenic effect. The data presented in the review generally give an idea of chitosan and its derivatives as very effective and promising plant protection products and biostimulants.